2014
DOI: 10.1098/rsbl.2014.0449
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic interaction between UVB radiation and temperature increases susceptibility to parasitic infection in a fish

Abstract: Levels of UVB radiation (UVB) and mean temperatures have increased substantially over recent decades in many regions of the world. Both stressors independently can compromise immune function, disease resistance and fitness in fish. The impact of UVB can also be exacerbated by interactions with environmental temperatures. In this paper, we test the hypothesis that UVB and temperature act synergistically to influence patterns of energy consumption and susceptibility to disease. We exposed mosquitofish, Gambusia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…Impacts of stressors including higher temperatures, reduced dissolved oxygen concentrations or water pollution have been largely considered separately but a growing body of literature shows that they may combine in various manners, including additive, antagonistic or synergistic interactions [2,3]. In a multiple stressors context, understanding how distinct pressures interact is critical to predict their consequences on ecosystems and develop efficient management and risk assessment tools [4].…”
Section: Introductionmentioning
confidence: 99%
“…Impacts of stressors including higher temperatures, reduced dissolved oxygen concentrations or water pollution have been largely considered separately but a growing body of literature shows that they may combine in various manners, including additive, antagonistic or synergistic interactions [2,3]. In a multiple stressors context, understanding how distinct pressures interact is critical to predict their consequences on ecosystems and develop efficient management and risk assessment tools [4].…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies of ecotoxicology and ecological disturbances have examined the nature of interactions in the laboratory [13][14][15] and in the wild [16,17]. Both synergistic [18][19][20][21][22][23][24][25] and antagonistic [23,[26][27][28][29] interactions have been uncovered in a wide range of organisms, environments and systems that range from gene epistasis [30][31][32] to predator-prey interactions [33].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence however, suggests that the effects of climate change can act in a synergistic fashion with UVB in fish (Cramp et al 2014) and bacteria alike (Li et al 2014). Despite the extensive literature on the consequences of exposure to UVR and protection mechanisms in other animals and plants, our knowledge about these important issues is limited in reef fish.…”
Section: Significance and Aimsmentioning
confidence: 99%
“…Kiesecker and Blaustein (1995), Long et al (1995) and Bancroft et al (2008)), relatively little is known about synergistic effects in the tropical marine environment (but see Lesser et al (1990) for a study on coral bleaching). On the individual level, the ability of reef fish to withstand UV exposure during development and the impact of UVR on young reef fish should be examined in further detail and under consideration of other stressors (elevated temperature and pH) which could act in synergy with UVR (Cramp et al 2014, Li et al 2014). Cramp (2014) showed that UVR in combination with elevated temperature increases parasitism and therefore risk of disease in freshwater fish.…”
Section: Synergistic Effects Of Uv and Other Environmental Stressors mentioning
confidence: 99%
See 1 more Smart Citation